Efeito de inibidores vegetais sobre o crescimento E o florescimento da grama-santo-agostinho - de Marchi, Sidnei Roberto; Martins, Dagoberto [UNESP]; da Costa, Neumárcio Vilanova (My University, 2015)
The objective of this work was to evaluate the effects of three plant growth inhibitors on the development and emission of floral rachis of Saint Augustine grass [Stenotaphrum secundatum (Walt.) Kuntzel] plants. The study was carried out in a 15 month old lawn with the experimental plots being distributed in accordance with a complete randomized block design with four replications. The treatments consisted of sole application of trinexapac-ethyl (113, 226, 452, 678, and 904 g ai ha-1), prohexadione-calcium (100 and 200 g ai ha-1), and bispyribac-sodium (40 and 60 g ai ha-1) plus a check treatment in which the plants were not submitted to any of the plant growth inhibitors. The effects of those products were evaluated in terms of visual signs of plant intoxication, plant height, emission and height of floral rachises, and chip total dry matter production. All the plant growth inhibitors resulted in visible injury to the plants but these intoxication signs practically disappeared 28 days after the application. Trinexapac-ethyl at the dose of 904 g ai ha-1 reduced plant height by 59.7%, the emission of floral rachis by 96.4%, and the amount of chip dry matter production by 87.7%. Plant growth inhibitors may reduce the number of times of lawn plants cutting up to 119 days after their application with no harmful effects on the plants visual aspect.
Effects of plant regulators on the growth and flowering of saint augustine grass plants
Keywords: Bispyribac-sodium; Prohexadione-calcium; Stenotaphrum secundatum; Trinexapac-ethyl